Analisis Perkembangan Pasar Uang Antar Bank Syariah (Studi Literatur) - Sitorus, Eva Afrilisa; Sari, Riska Dwi; Situmorang, Nurul Utami; Nuraini, Nuraini; Harahap, Muhammad Ikhsan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study is to analyze the development of the Islamic interbank money market. This study was examined qualitatively by using literaturreview which discusses the development of the Islamic interbank money market. Then the article is analyzed using the content analysis. The results show that the coefficient R2 (R Squared) of 0.923063 states that the variables of minimum mandatory current account, current account balance, third party funds, and secondary reserve are able to explain the variation of the interbank money market by 92.30% while the remaining 7.70% is explained by other factors outside the model.This is based on several studies on the development of the Islamic interbank money market.